Application of holographic meridian scraping therapy in the treatment of chloasma (全息经络刮痧在黄褐斑治疗中的应用) - HU Hairong (胡海荣); WANG Liangmin (王梁敏); XU Bing (许冰); TIAN Yajuan (田亚娟); TANG Ling (唐玲) (中西医结合护理)
The holographic meridian scraping therapy is a healing technique which can dredge the qi and blood, improve the microcirculation, get rid of toxins and other metabolites, it is convenient to use, with obvious curative effect and less adverse reactions. Chloasma is an acquired pigmentation dermatosis leading excess symmetry pigmentation in face and neck. It is an influencing factor of facial beauty and psychological stress. This paper briefly discussed the application of holographic meridian scraping therapy in the treatment of chloasma. (全息经络刮痧美容是通过对脏腑、气血、面部同时调理, 调内以美外, 达到标本兼治, 美丽与健康兼得的效果, 具有简便易行、效果明显且无不良反应的特点, 被称为中医美容技法精粹。黄褐斑是发生于面部的一种色素沉着性皮肤病, 不仅影响美观, 还会增加患者心理压力。本文对全息经络刮痧法用于黄褐斑治疗的实践效果进行观察, 旨在为黄褐斑治疗提供思路和方法。)